Hidden causality in Modern Greek - Tsilia, Anastasia (Natural language semantics, 2025)
This paper explores the syntax and semantics of an attitudinal construction in Modern Greek ( mg ), where an attitude verb takes an accusative object followed by a complement clause. Building on existing syntactic literature (e.g., Hadjivassiliou et al. in 13th international symposium on theoretical and applied linguistics, Aristotle University of Thessaloniki, Thessaloniki, pp. 70–80, 2000 ; Kotzoglou in Reading Working Papers in Linguistics 6:39–56, 2002 ; Kotzoglou in Selected papers on theoretical and applied linguistics from 22nd ISTAL, Aristotle University of Thessaloniki, Thessaloniki, pp. 299–315, 2017 ; Kotzoglou and Papangeli in New horizons in the analysis of raising and control, Springer, Dordrecht, pp. 111–131, 2007 ), I show that the accusative object is base-generated higher than the lower clause. Yet, I show that it semantically behaves as if it is part of the intensionalized argument of the attitude verb, giving rise to de dicto readings (Tsilia in Proceedings of Sinn und Bedeutung 27, pp. 655–673, 2023 ). Building on this and on a causal semantic requirement associated with the accusative object, I suggest a clausal analysis of the phenomenon. More specifically, under this analysis the accusative object is the subject of a small intermediate vp clause headed by a silent proleptic cause , which then takes the complement clause as its object. This contributes to the literature suggesting that hidden clauses are cross-linguistically attested and can solve intensionality paradoxes (den Dikken et al. in Non-propositional intentionality, Oxford Academic, Oxford, pp. 46–94, 2018 ), as well as to the literature on prolepsis (Davies in Language 81:645–665, 2005 ; Salzmann in The Wiley-Blackwell companion to syntax, Blackwell, Malden, vol. 5, pp. 3203–3245, 2017a ; Deal in Semantics and Linguistic Theory 28:622–648, 2018 ; Dawson and Deal in Proceedings of Sinn und Bedeutung 23, pp. 329–346, 2019 ) showing that proleptic constructions may have varying interpretations and syntactic analyses cross-linguistically.